Assessment of biochemistry request forms - Singh, S; Khatiwada, S (Journal of Chitwan Medical College, 2017)
Oversight of information on biochemistry requisition forms may lead to laboratory errors. The aim of this study was to evaluate the level of completion of these forms. The observational cross-sectional study was conducted between December 2014 and March 2015 in the biochemistry department of a tertiary hospital in Kathmandu after approval by the Institutional Ethical Review Committee. Two thousand and thirty nine request forms were randomly assessed for the completeness of information provided by the requesting physician. Microsoft excels software and SPSS-17 was used for analysis. Patient confidentiality was maintained. Out of 2039 request forms examined, the only 100% documented parameter was the patient’s name. Date of specimen collection was recorded in 79.74% of forms and age in 98.53%. The working diagnosis was recorded in 28.44% but no information regarding patient preparation. While the consultants name were stated in 13.29% of cases, drug history in 0.24%. Parameters like gender were recorded in 98.82%, sample type in 0.29%. Whether the patient was present in the ward or in the outpatient department was documented in 15.11% whereas patient number in 38.35%. Doctors were more likely to sign the forms rather than providing their name/designation. This study demonstrates that the custom of completion of request forms was poor. As laboratory data plays a significant role in medical diagnosis and research, incomplete data provided to the laboratory could significantly impact on the comments and successful outcome of treatment. Closer interaction between clinicians and laboratory personnel by means of request forms can improve the quality of services to patients.